2020
DOI: 10.1016/j.heliyon.2020.e04966
|View full text |Cite
|
Sign up to set email alerts
|

Predicting residents' intention to conserve the hooded vulture (Necrosyrtes monachus) in the Birem North District, Ghana

Abstract: The vulture as an important and specialized scavenger in human societies, helps clean the environment and prevents diseases. However, plummeting populations across the globe in the last three decades has led to the classification of some species as endangered and critically endangered. This study predicts the intention of residents to support conservation of the hooded vulture in communities near a mine site in the Eastern region of Ghana. Novelty of the current study lies in the use of a social psychology the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The study revealed that subjective norms and entrepreneurial intentions constructs having the insignificant relationships (Arafat et al, 2020;Doanh & Bernat, 2019;Mfazi & Elliott, 2022). But According to TPB theory subjective norm has significant influence on entrepreneurial intension (Wijerathna et al, 2015;Kankam & Abukari, 2020) This study concluded with a positive relationship between PBC and EI with a path coefficient of 0.554.…”
Section: Subjective Norm and Student's Entrepreneurial Intensionmentioning
confidence: 79%
See 1 more Smart Citation
“…The study revealed that subjective norms and entrepreneurial intentions constructs having the insignificant relationships (Arafat et al, 2020;Doanh & Bernat, 2019;Mfazi & Elliott, 2022). But According to TPB theory subjective norm has significant influence on entrepreneurial intension (Wijerathna et al, 2015;Kankam & Abukari, 2020) This study concluded with a positive relationship between PBC and EI with a path coefficient of 0.554.…”
Section: Subjective Norm and Student's Entrepreneurial Intensionmentioning
confidence: 79%
“…According to Wijerathna et al (2015), the most important variables affecting agricultural students' entrepreneurial intentions in Sri Lanka are subjective norm and attitudes. However, in their research in the eastern region of Ghana, Kankam and Abukari (2020) pointed out that attitudes and subjective norm seem to be good indicators of intentions than perceived behavioural control.…”
Section: Subjective Norms (Sn) and Entrepreneurial Intention (Ei)mentioning
confidence: 97%
“…The favorable stakeholders' attitude positively shapes the trajectory of performance of the vulture conservation, and brings about affirmative stakeholder social change for sustaining vulture populations [ 79 ]. Social capital can leverage paucity of forensic field protocols, and essential storage and testing facilities [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are published works on vulture populations and the related threats to their conservation in study areas such as game reserves [9], urban settlements [6], wildlife markets [10], and places outside protected areas [11], in Nigeria. However, there is a paucity of published data on vulture populations in protected areas under IUCN category II in Nigeria.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, depriving conservation biologist the advantage of strategic and pre-emptive planning to outwit and deny wildlife profiteers access to the vultures. According to [5], [6], there is ample evidence of transborder trade in wildlife species including vultures. The vagaries of anthropogenic stressors following intense land use modifications and vulture removals from landscapes are loading the odds against precision surveillance and adaptive conservation of the critically endangered vultures in PAs of Nigeria.…”
Section: Introductionmentioning
confidence: 99%